Clover root weevil in the South Island detection response and current distribution - Phillips, C.B.; McNeill, M.R.; Hardwick, S.; Vink, C.J.; Kean, J.M.; Bewsell, D.; Ferguson, C.M.; Winder, L.M.; Iline, I.I.; Barron, M.C.; Stuart, B. (New Zealand Plant Protection, 2007)
Sitona lepidus had spread throughout the North Island of New Zealand by 2005 and was first detected in the South Island in January 2006 when one individual was found at Harewood Christchurch Intensive sampling during February 2006 recovered only two additional specimens Several specimens were recovered from a separate Christchurch location in August 2006 Localised S lepidus populations were discovered near Richmond Nelson in April 2006 and in Rai Valley in May 2006 A website established in May 2006 to provide information about S lepidus was visited a mean of 135 times per month but it was never used to report possible new South Island infestations A biological control agent Microctonus aethiopoides was released at Richmond and Rai Valley between August 2006 and March 2007 By May 2007 it was parasitising from 4 to 14 of S lepidus adults which indicates it is likely to become permanently established